Pengaruh Harga dan Lokasi terhadap Minat Beli Ulang: Peran Keputusan Pembelian - Darma Wijaya; Purwatiningsih Purwatiningsih; Sopyan Sopyan; Iwan Iwan (Universitas Nusantara PGRI Kediri, 2024)
This study aimed to investigate the effects of location and price on repurchase interest in decisions made at Tangerang City's Madura grocery stalls. This study used a descriptive empirical approach by taking an intencional sampling of one hundred Madura grocery stall customers. The data were analyzed using Partial Least Square (PLS) path analysis. The research found that price and location have a major influence on purchasing decisions; In addition, purchasing decisions serve as important mediators in the relationship between price and repurchase interest, as well as location and repurchase interest. The conclusion of this study is that Madurese grocery stalls must maintain strategically affordable prices and locations to drive customers' repurchase decisions and interests. To explore the factors influencing the popularity of Madura grocery stalls, future research may consider factors such as service quality.